TINGKAT PERSEPSI PENGUNJUNG TERHADAP DESTINASI MICE KABUPATEN BOGOR - Firman Syah (Bisnis Event, 2023)
Some activities including MICE are accommodation. As lodging, in addition to being used by visitors for resting at night, some accommodations can provide a meeting room or for other events that can add value to a destination. In Bogor Regency itself, visitors who have tried to hold MICE activities have a different view of the venues that are suitable for holding MICE activities. The results of the research using quantitative methods, explained that although there were differences in choosing venues, they agreed that Bogor Regency would be an ideal destination for organizing MICE activities. Because, each region has a unique and distinctive venue characteristics. Another reason for compatibility of destinations in Bogor Regency is the tourist attraction based on leisure. So that visitors can enjoy a short vacation time on the sidelines of the main agenda. No wonder when every district has more than one tourist destination.